Effect of Planting Media and Dose of Goat Manure on the Growth and Yield of Lettuce in the Urban Faming System - Tassha Junaidi; Setyono Yudo Tyasmoro (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2022)
The high population and the lack of productive land in Indonesia cause environmental problems caused by pollution and waste. Urban farming could be a solution to provide food needs and can also improve urban environmental conditions. Lettuce are suitable for cultivation in urban areas, the taste and benefits make lettuce have good prospects. Reusing waste such as roasted husks and goat manure as fertilizer also beneficial for the environment. This research aimed to study the best combination of media and dosage of goat manure and its effect on increasing lettuce growth and yield. The hypothesis is that the application of goat manure can increase the growth and yield of lettuce and the difference in yield between the combinations of planting media on lettuce. The research was conducted from October to December 2020 at Greenhouse CV. Kurnia Kitri Ayu. This research used a Randomized Block Design with 10 treatment combinations. P1: Soil + 0 g, P2: Soil + 25 g, P3: Soil + 50 g, P4: Soil + 75 g, P5: Soil and Roasted Husk (2:1) + 25 g, P6: Soil and Roasted Husk (2:1) + 50 g, P7: Soil and Roasted Husk (2:1) + 75 g, P8: Soil and Roasted Husk (1:1) + 25 g, P9:Soil and Roasted Husk (1:1) + 50 g, and P10: Soil and Roasted Husk (1:1) + 75 g. The combination of planting media and goat manure can support the growth of lettuce compared to the use of media without the combination and addition of manure. P7 and P9 have the best results, the highest average is giving P7 treatment with an average weight of 44.67g and an average economic weight of 40.67g.